Performance evaluation of computer and communication systems milestones and future challenges ; IFIP WG 6.3/7.3 International Workshop, PERFORM 2010 in Honor of Günter Haring on the Occasion of his emeritus celebration Vienna, Austria, October 14-16, 2010, revised selected papers - Haring, Günter 1943-.; Hummel, Karin Anna.; Hlavacs, Helmut; Gansterer, Wilfried; SpringerLink (Online service). (Heidelberg New York Springer, 2011)
This Festschrift volume is published in honor of Günter Haring on the occasion of his emerital celebration and contains invited papers by key researchers in the field of performance evaluation presented at the workshop Performance Evaluation of Computer and Communication Systems - Milestones and Future Challenges, PERFORM 2010, held in Vienna, Austria, in October 2010. Günter Haring has dedicated most of his scientific professional life to performance evaluation and the design of distributed systems, contributing in particular to the field of workload characterization. In addition to his own contributions and leadership in international research projects, he is and has been an excellent mentor of young researchers demonstrated by their own brilliant scientific careers. The 20 thoroughly refereed papers range from visionary to in-depth research papers and are organized in the following topical sections: milestones and evolutions; trends: green ICT and virtual machines; modeling; mobility and mobile networks; communication and computer networks; and load balancing, analysis, and management.
Disappointments and Delights, Fears and Hopes Induced by a Few Decades in Performance Evaluation.-  Model Interoperability for Performance Engineering: Survey of Milestones and Evolution -- Tools for Performance Evaluation of Computer Systems: Historical Evolution and Perspectives -- Energy: A New Criteria for Performances in Large Scale Distributed Systems -- From the Origins of Performance Evaluation to New Green ICT Performance Engineering -- Predicting Disk Scheduling Performance with Virtual Machines -- Modeling Wireless Sensor Networks Using Finite-Source Retrial Queues with Unreliable Orbit -- Markov Chains and Spectral Clustering -- On the Analysis of Queues with Heavy Tails: A Non-extensive Maximum Entropy Formalism and a Generalisation of the Zipf-Mandelbrot Distribution -- Performance Evaluation with Hidden Markov Models -- Network Protocol Performance Bounding Exploiting Properties of Infinite Dimensional Linear Equations -- Modelling Social-Aware Forwarding in Opportunistic Networks -- On Lookahead Strategy for Movement-Based Location Update: A General Formulation -- Bayesian Estimation of Network-Wide Mean Failure Probability in 3G Cellular Networks -- Time Is Perception Is Money ? Web Response Times in Mobile Networks with Application to Quality of Experience -- On Traffic Domination in Communication Networks -- Improving Clustering Techniques in Wireless Sensor Networks Using Thinning Process -- AWPS ? An Architecture for Pro-active Web Performanc Management -- Analysis of Web Logs: Challenges and Findings -- A Matrix-Analytic Solution for Randomized Load Balancing Models with PH Service Times.
Electronic reproduction.
Keywords: Computer systems -- Evaluation -- Congresses; Telecommunication systems -- Evaluation -- Congresses; Electronic books